Back-To-Back Houses in Twenty-First Century Leeds. (3rd April 2019) - Harrison, Joanne
ABSTRACT: This research examines the significance of the Victorian and Edwardian back-to-back houses in Leeds and whether the built heritage (plan-form typology, urban character, style, traditional materials and construction) might be at risk. The methodology is based on a historic area assessment of the Harehills district. The development of the area is traced from historic maps and archival documents, and is supplemented with a survey of the houses. The plan-form typologies and decorative designs are identified, and mapped to show groups of like houses, which cross-references to a gazetteer detailing the main identifying features of each group. A second level of analysis is concerned with the houses as they stand today, focusing particularly on the extant decorative features and construction materials, the modifications that have compromised the architectural composition of the houses, and the uniformity of the urban setting. The research concludes that the back-to-back houses do have heritage significance, but a review of national and local policy reveals that this has never been recognised. The lack of protection has resulted in diminished significance and presents an ongoing risk. Suggestions are made for future research and protection strategies.